2006
DOI: 10.1111/j.1600-0609.2006.00692.x
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib increases osteoblast activity in myeloma patients irrespective of response to treatment

Abstract: These data show that treatment with bortezomib leads to enhanced markers of osteoblast activity in patients with myeloma. The comparison with the control group suggests that the effect on osteoblasts is unique to the proteasome inhibitor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
105
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(112 citation statements)
references
References 32 publications
(33 reference statements)
6
105
0
1
Order By: Relevance
“…20 Recent studies demonstrated that bone markers, which reflect osteoclast and osteoblast activity, can be modulated by novel agents such as proteasome inhibitors or immunmodulatory drugs. [21][22][23][24] Because of the clinical relevance of myeloma bone disease, we hypothesized that the bone resorption marker ICTP may add to the prognostic value of ISS. Thus, we evaluated the adverse prognostic impact of ICTP in combination with established prognostic factors in a patient cohort of 100 consecutive newly diagnosed patients with symptomatic MM.…”
Section: Introductionmentioning
confidence: 99%
“…20 Recent studies demonstrated that bone markers, which reflect osteoclast and osteoblast activity, can be modulated by novel agents such as proteasome inhibitors or immunmodulatory drugs. [21][22][23][24] Because of the clinical relevance of myeloma bone disease, we hypothesized that the bone resorption marker ICTP may add to the prognostic value of ISS. Thus, we evaluated the adverse prognostic impact of ICTP in combination with established prognostic factors in a patient cohort of 100 consecutive newly diagnosed patients with symptomatic MM.…”
Section: Introductionmentioning
confidence: 99%
“…93,94 As described by Heider et al, the combination of bortezomib ± dexamethasone produced significant increases in serum bALP and OC in both responders and non-responders. 95 Giuliani et al found significant increases in the number of osteoblasts per mm 2 of bone tissue in trephine biopsies of patients responding to bortezomib, but not in subjects who did not respond. 96 Terpos et al showed that, in 34 patients bortezomib monotherapy reduced serum Dkk-1 and RANKL levels.…”
Section: Bortezomibmentioning
confidence: 99%
“…Indeed, Heider et al found an attenuated increase in bALP in patients who received VD compared with those who received bortezomib monotherapy. 95 Thus, although different effective anti-myeloma regimens in combination with bisphosphonates can reduce bone resorption through reduction of tumor burden and inhibition of osteoclast function, 63 to-date only bortezomib has clearly shown an anabolic bone effect in MM.…”
Section: Bortezomibmentioning
confidence: 99%
“…Osteoblast stimulation by bortezomib was also reported by Heider et al, 87 who measured changes in bALP and OC, in patients who received bortezomib7dexamethasone (n ¼ 25) and in a control group of patients who received adriamycin/ dexamethasone, melphalan/prednisone or thalidomide-containing therapy (n ¼ 58). Significant increases in bALP and OC following bortezomib treatment were observed in both responders and non-responders, irrespective of whether dexamethasone was included in the treatment regimen.…”
Section: Clinical Studiesmentioning
confidence: 93%